Genetic Factors and Purine Consumption as Predictors of Uric Acid in Coastal Communities - Irma; Yulanda, Ellen; Liaumin Azim, La Ode; Kamrin, Kamrin (Window of Health : Jurnal Kesehatan, 2023)
The incidence of uric acid in the world is estimated at 47.2% which varies in various populations throughout the world. The highest prevalence of uric acid in people aged >15 years, according to districts/cities in Southeast Sulawesi Province, based on doctors' diagnoses, was in North Buton (12.62%). therefore, North Buton District, especially in the working area of ​​the Kulisusu Health Center was chosen as the location of this study. This study aims to determine the predictors of uric acid in people in coastal areas. This study uses a case-control study design. The population in this study consisted of people living in the coastal area of ​​the Kulisusu Health Center, with a total sample of 106 (53 cases and 53 controls). Sampling using a simple random sampling technique. Data was collected using a questionnaire, and the data that had been collected was analyzed statistically using the chi-square test at a 95% confidence level (α = 0.05) which aims to analyze predictors of gout. The results showed that genetic factors had a value (p=0.004; OR=3.559; CI = 1.483-8.539) and purine consumption patterns had a value (p=0.02; OR=3.103; CI=1.162-8.288). It can be concluded that genetic factors and purine consumption patterns are predictors or risk factors for gout in coastal communities in the working area of ​​the Kulisusu Health Center. Coastal communities should limit foods that contain high purines, such as shellfish and meat, especially for those who have a family history of uric acid.